Biochips—New Platforms for Cell‐Based Immunological Assays. Issue 1 (18th December 2017) - Shao, Ning; Qin, Lidong
Abstract: Considerable advances have been witnessed in the development of biochips that seek to realize various types of immune cell analysis on microscale platforms and enhance both basic and applied immunological research beyond the capability of conventional methods. Here, state‐of‐the‐art designs and examples for biochip‐based analysis and manipulation of immune cells are reviewed, and the potential of this emerging technology to enhance the understanding of immunology and improve disease diagnosis and treatment is discussed. In particular, some of the recent advances in this field, along with the challenges that must be addressed for these technologies, and their potential in precision medicine are highlighted. Abstract : The applications of biochips in cell‐based immunological assays are reviewed, with recent advances highlighted. An overview of biochip‐based platforms for immune cell assays of secretion, cytotoxicity and migration, and for immune cell cytometry and engineering are presented. Potentials and challenges of these technologies in fundamental and applied immunology are also discussed.